A just and equitable water future for all in an ever-changing environment: An urgent call for accelerated actions - Sunil K. Sinha; Pierre Glynn; Paolo Gardoni; Pingbo Tang; Meghna Sebens; Caitlin Dyckman; Jennifer Helgeson; Jeffrey Berk; Kenneth Thompson; William Williams; Walter Graf; Srini Vallabhaneni; et al. (Cambridge Prisms: Water)
Access to clean and reliable water is critically important for health, well-being, and economic development. The natural, built, and social systems – which interact with each other and comprise the water system-of-systems – are threatened by intensifying hazards and stressors like crumbling infrastructure, floods, droughts, storms, wildfires, sea level rise, population growth, cyber threats, and pollution. Marginalized communities, including disadvantaged and rural communities and Tribal nations with insufficient access to clean water or regenerative sources of water, are often the most impacted. Responses to these issues are hampered by fragmented and uncoordinated governance and management. A multi-stakeholder structured engagement process at the SWIM conference and workshop held in December 2023 identified the most critical current and future issues facing the water sector and what needs to change to find solutions. This paper synthesized these issues. Highlighted issues were the vulnerability and lack of resilience of water systems to hazards and stressors, inequities associated with water scarcity, and water quality problems – all affected by climate change, land-use change, and socio-economic changes. The Smart One Water (S1W) vision provided an important context for the conference. This paper expands the S1W vision with a synthesis of discussions about S1W-related fundamental concepts, practices, and implementation barriers.